2021
DOI: 10.18203/2394-6040.ijcmph20212031
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual hygiene practices among adolescent girls in rural area of India

Abstract: Menstruation and menstrual practices still face many social, cultural, and non secular restrictions which is an enormous barrier within the path of menstrual hygiene management. In many parts of the country especially in rural areas girls aren't prepared and aware of menstruation in order that they face many difficulties and challenges reception, schools, and work places. In rural areas, women don't have access to sanitary products or they know little about the kinds and method of using them or are unable to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 3 publications
0
0
0
Order By: Relevance
“…According to research conducted in Nepal, age has a significant influence on a person's menstrual practices [9]. This is also in line with research conducted in Belgaum that there is a significant relationship between age and hygiene practices during menstruation [10]. This is supported by research conducted in Western Ethiopia that found that adolescents with more than 18 years of age are more vigilant regarding menstrual hygiene than adolescents aged less than 18 years [11].…”
Section: Factors Affecting Personal Hygiene Practice During Menstruationsupporting
confidence: 67%
See 2 more Smart Citations
“…According to research conducted in Nepal, age has a significant influence on a person's menstrual practices [9]. This is also in line with research conducted in Belgaum that there is a significant relationship between age and hygiene practices during menstruation [10]. This is supported by research conducted in Western Ethiopia that found that adolescents with more than 18 years of age are more vigilant regarding menstrual hygiene than adolescents aged less than 18 years [11].…”
Section: Factors Affecting Personal Hygiene Practice During Menstruationsupporting
confidence: 67%
“…Mother's Role as Educator Highly educated parents, especially mothers, are expected to provide information related to proper menstrual practices to their children because mothers are generally close to their children. This statement is supported by the results of research conducted in Belgaum that there is a significant relationship between the mother's education level and good menstrual practices [10] In a study conducted on adolescents in Depok, it was also found that there was a significant relationship between the role of mothers as educators related to menstruation and menstrual hygiene practices in adolescent girls [16].…”
Section: Factors Affecting Personal Hygiene Practice During Menstruationmentioning
confidence: 75%
See 1 more Smart Citation